Mozambique : Country Economic Memorandum, Sustaining Growth and Reducing Poverty - World Bank (Washington, DC, 2012)
Mozambique has staged a dramatic recovery from the damage of the civil war, improving infrastructure nearly to pre-war levels; reducing poverty from 69 to 54 percent; growing the economy by 8 percent annually between 1996 and 2003; expanding the agricultural, tourism construction and manufacturing sectors; and attracting mega-projects in aluminum smelting, natural gas, and titanium mining, and this tripling exports. Another factor which was a precondition for all of the above is the fact that the country was successful in bringing about reconciliation, ending the civil war, and in managing potential conflicts since that time. Mozambique has just had its third general and presidential election. Nevertheless the country remains poor, infrastructure is inadequate, there are serious unmet education and health needs, and poverty rates remain high. This Memorandum examines the growth-poverty linkage, using a wide variety of data sources, including the recently completed national household survey (2002/3). It has sought to understand the sources of growth in the recent past, to evaluate the prospects for growth in the next decade, to examine the likely implications for poverty, and to outline the policies that will be needed to achieve further growth and poverty reduction. The Country Economic Memorandum also examines the relevance of natural resource management to growth and poverty objectives.